Fine mapping of a region on chromosome 21q21.11–q22.3 showing linkage to type 1 diabetes. Issue 1 (5th January 2005) - Bergholdt, R; Nerup, J; Pociot, F
Abstract : Background: Results of a Scandinavian genome scan in type 1 diabetes mellitus (T1D) have recently been reported. Among the novel, not previously reported chromosomal regions showing linkage to T1D was a region on chromosome 21. Objective: To fine map this region on chromosome 21. Methods and results: The linked region was initially narrowed by linkage analysis typing microsatellite markers. Linkage was significantly increased, with a peak NPL score of 3.61 (p = 0.0002), suggesting the presence of one or several T1D linked genes in the region. The support interval for linkage of 6.3 Mb was then studied by linkage disequilibrium (LD) mapping with gene based single nucleotide polymorphisms (SNPs). Thirty two candidate genes were identified in this narrowed region, and LD mapping was carried out with SNPs in coding regions (cSNPs) of all these genes. However, none of the SNPs showed association to T1D in the complete material, whereas some evidence for association to T1D of variants of the TTC3, OLIG2, KCNE1, and CBR1 genes was observed in conditioned analyses. The disease related LD was further assessed by a haplotype based association study, in which several haplotypes showed distorted transmission to diabetic offspring, substantiating a possible T1D association of the region. Conclusions: Although a single gene variant responsible for the observed linkage could not be identified, there was evidence for several combinations of markers, and for association of markers in conditioned analyses, supporting the existence of T1D susceptibility genes in the region.